2003
DOI: 10.1046/j.1365-2141.2003.04291.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival implications of molecular heterogeneity in variant Philadelphia‐positive chronic myeloid leukaemia

Abstract: Summary. The BCR-ABL fusion in chronic myeloid leukaemia (CML) is generated by the Philadelphia (Ph) translocation t(9;22) or, in 10% of patients, variants thereof (vPh). Deletion encompassing the reciprocal product (ABL-BCR) from the derivative chromosome 9 [der(9)] occurs in 15% of all patients, but with greater frequency in vPh patients. Reports of physical separation of ABL-BCR in nondeleted patients, as well as evolution from classical to variant Ph, introduce further heterogeneity to the vPh subgroup and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 39 publications
4
50
1
Order By: Relevance
“…In a study including Chinese patients with CML, Philadelphia positive cases (70.4%) demonstrated typical FISH pattern; 29.6% had atypical FISH pattern with 12 different types [12]. The frequency of atypical FISH patterns is comparable to the 15% reported by Cohen et al [19] and Reid et al [20]. In our study, 8% of patients with CML had atypical FISH patterns that the atypical FISH patterns were due to variant translocation; atypical BCR/ABL fused gene rearrangements on chromosome 9 or 9q deletion of the rearranged chromosome 9; coexistence of der(9q) and der(22q) deletions.…”
Section: Discussionsupporting
confidence: 66%
“…In a study including Chinese patients with CML, Philadelphia positive cases (70.4%) demonstrated typical FISH pattern; 29.6% had atypical FISH pattern with 12 different types [12]. The frequency of atypical FISH patterns is comparable to the 15% reported by Cohen et al [19] and Reid et al [20]. In our study, 8% of patients with CML had atypical FISH patterns that the atypical FISH patterns were due to variant translocation; atypical BCR/ABL fused gene rearrangements on chromosome 9 or 9q deletion of the rearranged chromosome 9; coexistence of der(9q) and der(22q) deletions.…”
Section: Discussionsupporting
confidence: 66%
“…These findings, albeit in only a small number of patients, contrast with the situation in CML, in which a higher incidence of deletions was demonstrated in those with variant Ph translocations. 23 One patient among the series with a single fusion signal showed, from a combination of FISH techniques, that the BCR/ ABL fusion had arisen from insertion of part of the ABL gene into chromosome 22, with no accompanying deletion of the corresponding sequences from the der (9). A number of cryptic insertions of either BCR into ABL at 9q34, as reviewed by Primo et al, 24 or rarely ABL into BCR at 22q11, 25 have been reported in CML, with the insertions confirmed by dual fusion FISH.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12]23 The poor outcome has been linked to patients with a visible deletion by FISH. Cases of Ph-positive CML have been reported, which lack expression of the ABL/BCR transcript but have no visible deletions.…”
Section: Discussionmentioning
confidence: 99%
“…6 This has been regarded as the explanation for the contradictory results obtained from survival analysis. 7 Recently, deletions in der(9) were observed in FISH deletion negative cases with quantitative PCR and we cannot exclude small deletions detectable only with PCR. 8 The lack of variant translocations in patients with deletions in our material could be a chance finding, as the expected number of such patients was only 4.…”
Section: To the Editormentioning
confidence: 99%